Plant-Associated Volatile Organic Compound (VOC) Database (PVD): A Resource Supporting Research on VOCs Produced by Plants and Plant-Associated Microbes - Danying Shao; Carl Schlagnhaufer; Ananda Bandara; Paul D. Esker; Seong H. Kim; Joshua Kellogg; Ji-Soo Jang; Seogchan Kang (PhytoFrontiers)
Diverse volatile organic compounds (VOCs) perform functions crucial for plant growth and health. However, studies on the nature and mechanisms of action of bioactive VOCs, except those mediating plant-insect interactions, lag considerably behind those on waterborne compounds. We built the Plant-Associated VOC Database (PVD) to facilitate research on VOCs released by plants and plant-associated microbes. This platform presents the physicochemical characteristics, biosynthetic pathways, and known or hypothesized functions of VOCs. We present the design, utility, and planned expansion of PVD. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.